Space charge limited current in a gap combined of free space and solid - Chandra, W. (2011)
The paper presents a model of the space charge limited (SCL) electron conduction in a gap with a combination of free space and dielectric solid. The SCL electron current density J is solved numerically to obtain the voltage scaling of J ∼ VGn, and n is found to be between n = 3/2 (a vacuum gap) and n = 2 (a dielectric diode). The dependence of n is calculated as a function of dielectric constant, electron mobility, and the relative length scale between the free space and dielectric solid. The model has been used to explain a recent experiment.